Keparahan Beberapa Penyakit Pada Buah Kakao di Perkebunan Rakyat Kecamatan Kumpeh Kabupaten Muaro Jambi - Enyla Manurung; Husda Marwan; Sri Mulyati (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2022)
This research aims to determine the severity of diseases found in cocoa plants (Theobroma cacao, L.) in people's plantations in Kumpeh Sub-district conducted in Sungai Bungur village, Pematang Raman village, Betung village, Petanang village, and Mekar Sari village. Sampling technique using purposive sampling method, plant samples are randomly selected in people's cocoa plantations. Observations are made on the symptoms of the disease in cocoa fruits caused by the disease. Then collected data by calculating all the fruits both healthy and diseases so that the percentage of plants attacked. Identification of disease pathogens is carried out in the Laboratory of the University of Jambi and in the Laboratory of the Village Quarantine Center of Agriculture Class I Jambi. The results showed that fruit anthrax disease is caused by Colletotrichum gloesporiodies and rotten fruit caused by Phytopthora palmivora. The severity of disease attacks in cocoa fruits is highest at 25.50 % and the percentage of disease is 58.00%.